1995
DOI: 10.1177/089686089501500106
|View full text |Cite
|
Sign up to set email alerts
|

Development of Toxic Degradation Products during Heat Sterilization of Glucose-Containing Fluids for Peritoneal Dialysis: Influence of Time and Temperature

Abstract: Objective Fluids for peritoneal dialysis (PD) cause cytotoxic reactions in many different in vitro systems. The low pH, the high osmolality of the fluids, and the glucose degradation products formed during heat sterilization have been considered responsible. In the present study, we investigate the influence of temperature and time during heat sterilization of PD fluids and glucose solutions on glucose degradation and cytotoxicity of the solutions. Design Ampoules containing PD-fluid or glucose solution were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Our results demonstrate that both 5-HMF and 2-FA are present in varying quantities in all injectable glucose solutions currently on the French market. Differences from one supplier to another may be explained by different sterilising processes (temperature, pressure and time of sterilization cycle) 1 , 6 , 35 , 36 . All suppliers confirmed the use of the moist heat method according to the European Pharmacopeia, but some did not provide their protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate that both 5-HMF and 2-FA are present in varying quantities in all injectable glucose solutions currently on the French market. Differences from one supplier to another may be explained by different sterilising processes (temperature, pressure and time of sterilization cycle) 1 , 6 , 35 , 36 . All suppliers confirmed the use of the moist heat method according to the European Pharmacopeia, but some did not provide their protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Kjellstrand et al . studied five different F 0 values and demonstrated that combining a high temperature with a short sterilisation time limited the formation of GDPs 36 . In our study, only one condition was close to those studied by Cook et al .…”
Section: Discussionmentioning
confidence: 99%
“…The process is substantially accelerated by exposure to high ambient temperatures. As commercially available PDF is heat sterilized, the degradation of PDF glucose occurs primarily during autoclaving and to a lesser extent also during prolonged storage (10–12). On the other hand, if PDF is sterilized by filtration, the levels of GDP generated are greatly diminished (13–15).…”
Section: Studies On the Role Of Glucose Degradation Products In Pdf Bmentioning
confidence: 99%
“…In particular, PD patients are exposed to hypertonic glucose solution on a long-term basis, which is not only toxic to mesothelial cells[ 6 , 71 ] but also promotes immune cell apoptosis[ 72 ]. Moreover, the high-temperature sterilization process produces GDPs such as methylglyoxal (MGO), acetaldehyde, formaldehyde, and 3-deoxyglucosone in PD dialysate[ 73 - 76 ]. GDPs possess strong oxidative properties and toxicity, and can induce AGEs[ 77 ].…”
Section: High Glucose and Gdp Increase Osmentioning
confidence: 99%